Non-Invasive Brain Stimulation: Enhancing Motor and Cognitive Functions In Healthy Old Subjects - Zimerman, Maximo; Hummel, Friedhelm C. (Frontiers in Aging Neuroscience, 2010)
Healthy aging is accompanied by changes in cognitive and motor functions that result in impairment of activities of daily living. This process involves a number of modifications in the brain and is associated with metabolic, structural and physiological changes; some of these serving as adaptive responses to the functional declines. Up to date there are no universally accepted strategies to ameliorate declining functions in this population. An essential basis to develop such strategies is a better understanding of neuroplastic changes during healthy aging. In this context, non-invasive brain stimulation techniques, such as transcranial direct current or transcranial magnetic stimulation, provide an attractive option to modulate cortical neuronal assemblies, even with subsequent changes in neuroplasticity. Thus, in the present review we discuss the use of these techniques as a tool to study underlying cortical mechanisms during healthy aging and as an interventional strategy to enhance declining functions and learning abilities in aged subjects.